Sebaran Pola Pertumbuhan Ikan Red Devil (Amphilophus sp) Di Kawasan Danau Batur, Bali - I Wayan Juliawan; I Wayan Arthana; Endang Wulandari Suryaningtyas (Bumi Lestari Journal of Environment, 2020)
Batur Lake is one of the lakes located in the Kintamani sub-district, Bali. This lake has abundant biodiversity, one of them is Red Devil fish (Amphilophus sp) which is a competitor of native and introduced fish. The research aims to find out the pattern of growth, size structure, and the physical and chemical conditions of waters. The method used was descriptive quantitative by using two trapping devices that were fishing rods and nets. Calculation results showed that a wide range of growth patterns of Red Devil (Amphilophus sp) fish on both trapping devices (fishing rods and nets) were grouped (Id<1). The highest sized structure value on the trapping devices (fishing rod) found in the water of Trunyan Village that was total length (TL) of 9,3 cm, Standard length (SL) of 7,3 cm, and weight: 16,5 gr. On the trapping devices (net) the highest value was found in the water of Songan Village that was total length (TL) of 13,5, SL of 11,1, and weight: 48,8 gr. The growth patterns of Red Devil (Amphilophus sp) fish based on length and weight analysis showed that were partly positive allometric and partly negative allometric. The result of the water quality measurement in the water of Batur Lake was about 26,3°C – 29,1°C (temperature), 5,36 mg/L – 6 mg/L, (DO), 7,2 – 7,8 (pH), and 87,1 cm – 147,8 cm (brightness).